New sheep and goat products: “Mantas” and sausages. An integrated project in co-promotion - Teixeira A.; Rodrigues S. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
A project between a research centre, two breeder associations and a meat manufacturing industry was developed to add value to animals with very low commercial acceptability, creating two new products, a raw fresh meat sausage and a processed meat product “manta”. The ratio between MUFA+PUFA/SFA was 1.54 g/100 g and 1.55 g/100 g of dry product and protein percentage 17.8%, and 18.8% for ewe and goat sausages, respectively. The most abundant unsaturated fatty acid was the C 18:1 and protein was 44.5 and 51% for ewe and goat “mantas, respectively. Both are balanced products in protein and fat contents resulting in an interesting solution to give added value to animals with very low commercial price.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)